Intranasal ovalbumin immunotherapy with mycobacterial adjuvant promotes regulatory T cell accumulation in lung tissues - AKKOÇ, TUNÇ (WILEY, 2018)
Allergen-specific immunotherapy to induce T regulatory cells in the periphery has been used to treat allergic diseases. Mycobacteria can be used as an adjuvant for inducing T regulatory cells. However, it is unclear whether intranasal immunotherapy in combination with Mycobacteria adjuvant induces regulatory T cell differentiation and attenuates allergic responses in vivo. To investigate the role of intranasal ovalbumin (OVA) treatment alone and in combination with Mycobacteria vaccae, proportions of FoxP3(+) regulatory T cells and anti-inflammatory responses were evaluated in a murine model of asthma that was established in three groups of bicistronic Foxp3(EGFP) reporter BALB/c mice. Before establishment of the asthma model, two groups of mice received intranasal OVA immunotherapy and one also received simultaneous s.c. M. vaccae. Expression of CD4(+)CD25(+)Foxp3(+EGFP+) T cells in the lung and spleen was analyzed by flow cytometry and the cytokine profiles of allergen-stimulated lung and spleen lymphocytes assessed. The intranasal OVA immunotherapy group showed greater expression of CD4(+)CD25(+)Foxp3(+EGFP+) T cells in the spleen whereas in the group that also received M. vaccae such greater expression was demonstrated in the lung. Additionally, the proportion of IL-10 and IFN--secreting splenocytes was greater in the intranasal OVA+M. vaccae group. CD25 neutralization decreased CD4(+)Foxp3(+) cells more than other groups. In parallel with this finding, production of IL-10 and IFN- was down-regulated. Mucosal administration of OVA antigen results in a greater proportion of CD4(+)Foxp3(+) T cells in the spleen. IL-10 and IFN- induced by intranasal OVA immunotherapy and M. vaccae administration is down-regulated after CD25 neutralization.
Keywords: allergen-specific immunotherapy; asthma model; BALB; c; Foxp3; Treg cells; VACCAE IMMUNIZATION; MURINE MODEL; INDUCTION; IL-10; MECHANISMS; TOLERANCE